Stem Cells and Their Cardiac Derivatives for Cardiac Tissue Engineering and Regenerative Medicine - Roshanbinfar, Kaveh; Esser, Tilman; Engel, Felix (Antioxidants & Redox Signaling, 2020)
Significance: Heart failure is among the leading causes of morbidity worldwide with a 5-year mortality rate of similar to 50%. Therefore, major efforts are invested to reduce heart damage upon injury or maintain and at best restore heart function.
CRIS-Team WoS Importer:2020-12-04